Synthesis and evaluation of metal lipoate adhesives - Ghosh, Animesh (2023)
The development of new bioadhesives with integrated properties remains an unmet clinical need to replace staple or suture. Current bioadhesives do not allow electronic activation, which would allow expansion into laparoscopic and robotic surgeries. To address this deficiency, voltage activated adhesives have been developed on both carbene and catechol-based chemical precursors. Herein, a third platform of voltage activated adhesive is evaluated based on lipoic acid, a non-toxic dithiolane found in aerobic metabolism and capable of ring opening polymerization. The electro-rheological and adhesive properties of lithium, sodium, and potassium salts of lipoic acid are applied for wet tissue adhesion. At ambient condition, potassium lipoate displays higher storage modulus than lithium or sodium salt under similar conditions. Voltage stimulation significantly improves gelation kinetics to Na- and K-lipoates, while Li-lipoate is found to not require voltage stimulation for gelation. Lap shear adhesion strength on wetted collagen substrates reveals that the synthetic metal lipoates have comparable adhesion strength to fibrin sealants without the viral or ethical risks.